AKTUALISASI IDENTITAS ETNIK TIONGHOA DALAM PERTUNJUKAN LIONG DI SEMARANG - Fawarti Gendra Nata Utami (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2018)
lndonesian political reform, which began in 1998, directly influenced the ethnic identity of the chinese community in Semarang. The Liong dance, as a chinese art form, began to be performed once again in the streets of Semarang’s China town, as part of parade to celebrate the anniversary of Hok Tek Tjing sien.The Liong dance means to give tangibility, to become an icon and metaphor, and to actualize various myths, beliefs, imagination, and world-views, which in reality are means of self-definition for a group or individual. A parade of a Liong dance, with its various symbols and attributes, with many Chinese people gathered together in one place, strengthens their social ties through symbols of their cultural system. This event is also a form communication, to show their identity, both as individuals and as a group, to the rest of the community and to those in power.Keywords: etnik, Tionghoa, pertunjukan, Liong, naga, Cina, identitas.